Minuman Berisotonik Berpengaruh Terhadap Sistem Kardiovaskuler Pada Aktivitas Fisik Anggota Medical Sport - Nurhikmawati, Nurhikmawati; Wisudawan, Wisudawan; Ikram, Dzul; Rachman, Ismi (Wal'afiat Hospital Journal, 2021)
Physical activity will increase the pulse rate caused by reduced oxygen consumption. Isotonic drinks are one way to restore lost body fluids so that the body avoids dehydration and extends muscle endurance. This study was conducted to determine the effect of isotonic drinks on the cardiovascular system on the physical activity of members of the medical sport FK-UMI. This research is research that uses a comparative analytical research design using a cross-sectional approach. Data analysis by comparing isotonic drinks and mineral water at 7 minutes was obtained (p less than 0.05). The results of the research showed that there was a significant difference in pulse rate, in which the recovery of pulse rate by giving isotonic drinks was better than the recovery of pulse rate by giving water. In this study, there was an effect of giving mineral water and isotonic drinks on the recovery pulse whereas isotonic drinks were better than the pulse recovery with water. The conclusion of the research is to know the effect of isotonic drinks on the cardiovascular system on the physical activity of members of the medical sport FK-UMI. It is recommended to apply the habit of consuming isotonic drinks when doing physical activities.